REKRUTMEN DAN SELEKSI STORE CREW DI PT. MIDI UTAMA INDONESIA, TBK. (BRANCH KENDARI) - Amalia Seha Wulandari; Haerani Nur (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
PT. Midi Utama Indonesia, Tbk. This is a company that has a number of branches spread throughout Indonesia and of course requires quality human resources (HR). The increase in the number of shops in various regions has resulted in a shortage of store crew at the Alfamidi Branch Kendari shop, resulting in the productivity of each shop continuing to increase. This causes work overload. To reduce workload, of course the company must have a number of employees that suits the company's needs, which can be done through a recruitment and selection process. Recruitment and selection stages at PT. Midi Utama Indonesia, Tbk carried out by independent campus internship students, namely People plan, disseminating job vacancy information, administrative selection, HRD interviews, psychological tests, and digital footprint. From the recruitment and selection activities carried out during the internship period, 389 applicants were received in February, 540 applicants in March and 656 applicants in April. There were 309 prospective candidates who passed the administrative selection stage in February, 364 applicants in March and 172 applicants in April. There were 168 candidates who went through the interview and psychological test selection stages in February, 51 applicants in March and 80 applicants in April for store crew positions who would then be invited for the training process. At the end of the recruitment and selection process through to training, there were 54 applicants in February, 72 applicants in March and 41 applicants in April who graduated to become store crew for Alfamidi Branch Kendari.